Ruthenium(II)–carbonyl complexes containing two N‐monodentate 1, 8‐naphthyridine ligands: active catalysis in transfer hydrogenation reactions. Issue 11 (26th October 2018) - Guajardo, Juana; Ibañez, Andrés; Guerchais, Veronique; Vega, Andrés; Moya, Sergio; Aguirre, Pedro
Abstract : cis ‐[RuCl2 {2‐(4‐methoxyphenyl)‐1, 8‐naphthyridine‐κ N 8 }2 (CO)2 ] and the 2‐methoxyphenyl derivative exhibit moderate catalytic activity with 100% selectivity for the hydrogen‐transfer reaction to acetophenone in the presence of a base. Abstract : The reaction of 2‐aminonicotinaldehyde with 2‐ or 4‐methoxyacetophenone in basic media leads to the new ligands 2‐(4‐methoxyphenyl)‐1, 8‐naphthyridine and 2‐(2‐methoxyphenyl)‐1, 8‐naphthyridine, respectively, in high yield. The reaction of these naphthyridine derivatives with [RuCl2 (CO)2 ] n leads to the respective complexes cis ‐dicarbonyldichloridobis[2‐(4‐methoxyphenyl)‐1, 8‐naphthyridine‐κ N 8 ]ruthenium(II) and cis ‐dicarbonyldichloridobis[2‐(2‐methoxyphenyl)‐1, 8‐naphthyridine‐κ N 8 ]ruthenium(II), both [RuCl2 (C15 H12 N2 O)2 (CO)2 ], in good yield. Both ruthenium(II) complexes display a slightly distorted octahedron with two cis carbonyl, two cis chloride and two cis naphthyridine ligands, the latter coordinated in a monodentate fashion through the N atom in the 8‐position. Both complexes exhibit a moderate catalytic activity in the hydrogen‐transfer reaction from propan‐2‐ol to acetophenone in the presence of a base, with 100% selectivity.